A framework for rural spatial governance based on the eco-environment oriented development mode: The case of coal mining subsidence area on the Weibei Plateau - Miaomiao Liu; Zhendong Lei; Ya Gao; Xue Li (Frontiers of Architectural Research)
The eco-environment-oriented development (EOD) mode is an innovative project organization and implementation approach that integrates ecological governance, industrial operations, and regional development. However, this mode still requires more in-depth research to strengthen its applicability to spatial perspectives and rural patterns. This study contributes to this context by proposing a rural spatial governance framework based on the EOD mode, focusing on the three main governance elements: space, capital, and subject. By constructing a conceptual model of the multidimensional governance effectiveness of EOD systems, it reveals the coupling mechanisms of three rural elements and proposes governance modes with spatially integrated optimization, capital value circulation, and rural subject connection as the focus of elemental regulation. This mode is further demonstrated through instantiation. In response to the developmental dilemmas of the villages’ overall decline owing to coal mining subsidence on the Weibei Plateau, an integrated transformation plan for production, living, and ecological spaces is formulated, based on which the stage-specific focuses are clarified in the holistic governance path of “space-capital-subject”. The research findings exemplify the application value and feasibility in regulating element relationships and balancing multiple benefits and can provide a reference at the spatial level to promote rural sustainable development through ecological governance.